Oxygen uptake at the lactate threshold in swimming - Morais, P.; Almeida, M.; Aleixo, I.; Corredoura, S.; Colaco, P.; Machado, L.; Fernandes, R.; Vilas-Boas, J. P. (Biomechanics and Medicine in Swimming X, 2006)
The purpose of this study is to identify, in terms of %VO2max, the intensity of swimming associated with a non linear increase of blood [La-]. Twenty nine swimmers participated in the study: 15 males and 14 females. Each subject performed a intermittent incremental protocol of 200m stages. The individual kinetics of the [La-]/ velocity and VO2 / velocity curves were taken in account for the assessment of lactate threshold (LT). The value of the [La-] corresponding to LT was 2.99±0.80mmol.l-1. In %VO2max, LA was 73.54±0.8%. This result seems to confirm that the best single [La-] value to predict LT, when testing trained swimmers, should be lower than the usual value of 4 mmol.l-1